Smart safety design for fire stairways in underground space based on the ascending evacuation speed and BMI. (May 2020) - Xie, Ruihang; Pan, Yin; Zhou, Tiejun; Ye, Wei
Highlights: Body mass index (BMI) has a significant effect on ascending evacuation speed. A prediction model of ascending evacuation speed according to BMI grouping. Smart safety design for fire stairways based on the prediction model. The smart system dynamically provides the best evacuation paths in fire stairways. Abstract: The evacuation problem in underground space restricts the large-scale development of underground space, wherein ascending evacuation is its main feature. Current evacuation regulations approaches for underground space generally suggest increasing dimension and number of evacuation paths and exits in architecture design plan, and no better way to improve the evacuation efficiency in underground space that has been built. This study aims to create a smart safety design for fire stairways to improve the evacuation efficiency without altering their architectural characteristics. The smart safety design is made up of two parts, one is the mathematical basis for predictable ascending evacuation speed of evacuees, and the other is the system logical architecture integrating intelligent devices. Therefore, firstly this study proved the relationship between the ascending evacuation speed in underground space and the body mass index (BMI) of a human. The experiment was completed by recruiting volunteers in a teaching building of a university in China. Ascending speed and BMI data were acquired through an observational experiment on individual ascending evacuation using stairways and by simulating an emergency in a 60 m underground environment. The relationship between ascending speed and BMI was analyzed via statistical method. A mathematical model of ascending speed change in different BMI groups was proposed for the ascending evacuation process in 0–60 m underground space. Then, the smart safety design for fire stairways in underground space was proposed based on the mathematical model. Weight sensors, height detectors, and pedestrian identification devices were designed in the same space at the entrance of the underground space and fire stairways. Base on the data from devices, the smart safety system could predict the change of density of occupants for each fire stairway through calculating ascending speed and BMI of occupants so as to suggest dynamic evacuation paths to evacuees. The smart safety design for fire stairways would improve the safety in underground space and promote sustainable development of underground space.